2015
DOI: 10.1002/aelm.201500183
|View full text |Cite
|
Sign up to set email alerts
|

Octonary Resistance States in La0.7Sr0.3MnO3/BaTiO3/La0.7Sr0.3MnO3 Multiferroic Tunnel Junctions

Abstract: General drawbacks of current electronic/spintronic devices are high power consumption and low density storage. A multiferroic tunnel junction (MFTJ), employing a ferroelectric barrier layer sandwiched between two ferromagnetic layers, presents four resistance states in a single device and therefore provides an alternative way to achieve high density memories. Here, an MFTJ device with eight nonvolatile resistance states by further integrating the design of noncollinear magnetization alignments between the ferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…MFTJ and related physics of multiferroic junctions have been actively investigated both theoretically and experimentally . Recently, it was demonstrated that by further considering noncollinear magnetization alignments between the FM layers, MFTJ device with eight nonvolatile resistance states can be realized . MFTJ opens a new pathway toward low power and higher density nonvolatile memory.…”
Section: Beyond Atomic 2d Semiconductorsmentioning
confidence: 99%
“…MFTJ and related physics of multiferroic junctions have been actively investigated both theoretically and experimentally . Recently, it was demonstrated that by further considering noncollinear magnetization alignments between the FM layers, MFTJ device with eight nonvolatile resistance states can be realized . MFTJ opens a new pathway toward low power and higher density nonvolatile memory.…”
Section: Beyond Atomic 2d Semiconductorsmentioning
confidence: 99%
“…Although MTJs have been the subject of intensive study due to their great potential for non-volatile magnetic memory applications, 1-3 moderate data storage density and especially a high-power consumption for controlling magnetisation still remain major challenges. To tackle those problems, several methods have been proposed including but not limited to utilising various non-collinear magnetization configurations in the ferromagnetic electrodes of semiconductor spin valves 4 or all-oxide MTJs, 5 manipulating domain states of ferromagnetic electrodes in pseudo spin valves, 6 or tuning tunnel barrier oxygen vacancies by voltage pulses in MgO-based MTJs. 7 Despite the aforementioned solutions, one promising candidate is multiferroic tunnel junctions (MFTJs), in which the ferroelectric/multiferroic layer is incorporated into a conventional magnetic tunnel junction (MTJ) as the tunnel barrier.…”
mentioning
confidence: 99%
“…If the spacer is not just a common insulator but a ferroelectric layer, the tunneling current will be controlled not only by magnetic field with different spin configurations, but also the applied electric bias that modifies the tunneling barrier by switching the polarization of the ferroelectric spacer . In this case, four states, or even more nonvolatile states, can be achieved at room temperature, which is important for designing novel high‐density information storage devices.…”
Section: Strategies For Controlling Functional Oxide Interfacesmentioning
confidence: 99%